Effect of Substrate on Egg Hatchability and Survival of Carp Seeds - Helmin Dupamana; Ade Muharam; Juliana Juliana (The NIKe Journal, 2020)
This study aims to determine the effect of different substrates on egg hatchability and survival of carp (Cyprinus carpio) seeds. This research is an experiment with 4 treatments and 3 replications. The treatment of addition of substrate is A (Fibers), B (Hydrilla), C (Raffia String), D (Control) Treatment. The design used is a Completely Randomized Design (CRD) using Analysis of Variance (ANOVA). Furthermore, further tests are carried out using the Least Significant Difference Test (LSD). The results obtained indicate that each treatment has a very significant effect. The highest hatchability was found in the palm substrate treatment of 87.66%, followed by the treatment of the raffia substrate 78.42%, then the control treatment with the percentage of hatching power was 64.78% and the lowest was in the hydrilla substrate treatment with the hatchability percentage of 57.51%. While the highest survival rate of tilapia fish was found in the treatment of palm oil substrate by 73.67%, and the survival rate with the lowest percentage was in the treatment of hydrilla sp. Substrate.